Setrategi Bersaing Dalam Kewirausahaan {Competitive Strategy On The Entrepreneurship} - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Sri Mulyati (Teknis, 2016)
To be the winner in the business world, we need competitive advantage strategy an entrepreneurÂ Â  had a very important role to created new wayÂ  that inovative and creative to reach a sustainable competitive advantage. Developments in the theory of competitive strategy, start from statis competitive strategy by Mitchale Potter continued with dinamis competitive strategy by Richard DâA vaniÂ  then comes the competitive strategy which focus on innovationÂ  were found by clayton christenses and kenici ohmae known as strategy 3C : customer, competitor and company. with the development of technology which Internet-based requires change strategy and connected strategy, like mark plus said known as 4C strategy and 5C strategy.Keywords: competitive advantage strategy , sustainable competitive advantage